Morphological Expressions of Crater Infill Collapse: Model Simulations of Chaotic Terrains on Mars. (29th October 2017) - Roda, Manuel; Marketos, George; Westerweel, Jan; Govers, Rob
Abstract: Martian chaotic terrains are characterized by deeply depressed intensively fractured areas that contain a large number of low‐strain tilted blocks. Stronger deformation (e.g., higher number of fractures) is generally observed in the rims when compared to the middle regions of the terrains. The distribution and number of fractures and tilted blocks are correlated with the size of the chaotic terrains. Smaller chaotic terrains are characterized by few fractures between undeformed blocks. Larger terrains show an elevated number of fractures uniformly distributed with single blocks. We investigate whether this surface morphology may be a consequence of the collapse of the infill of a crater. We perform numerical simulations with the Discrete Element Method and we evaluate the distribution of fractures within the crater and the influence of the crater size, infill thickness, and collapsing depth on the final morphology. The comparison between model predictions and the morphology of the Martian chaotic terrains shows strong statistical similarities in terms of both number of fractures and correlation between fractures and crater diameters. No or very weak correlation is observed between fractures and the infill thickness or collapsing depth. The strong correspondence between model results and observations suggests that the collapse of an infill layer within a crater is a viable mechanism for the peculiar morphology of the Martian chaotic terrains. Key Points: We investigate with DEM whether the chaotic terrains (CT) surface morphology may be a consequence of the collapse of the infill of a crater Model predictions and morphology of CT show strong similarities in terms of number of fractures and their correlation with crater diameters The correspondence between models and observations suggests that the collapse of a subice lake is viable for the chaotic terrains